The reliability of users of the financial statements produced by accounting information systems software determines the credibility of those statements - Abdul Wahab Abdul Razak Hassan Shwailih (Iraqi Journal for Administrative Sciences, 2024)
This study was born to measure the impact of the admissibility of the results of accounting information systems computerized among investors and potential customers who are trading accounting data through the financial statements of the economic units, and through review and explore reality in terms of the availability of quality specifications, and provide the ability and the means available to meet the needs and desires of the users of financial reports, and the extent of the keeping up with the technological developments in order to promote a clear vision of dimensions in the evaluation of telecom systems and thus breeding out the contentment and make appropriate recommendations, and through a review of scientific research in this field was the formulation of a model study variables and hypotheses and the identification and resolution organization. Overall analysis and interpretation of the results was centered in the following: 1) the availability of qualitative characteristics in computerized accounting information systems, but to varying degrees, 2) the availability of an item to keep pace with development, efficiency and practical experience with programming companies, 3) There is a great relationship between the availability of quality properties in computerized accounting information systems and the ability of these computerized systems to meet the needs and desires of the users of the results of those systems, 4) The above does not prevent the existence of disparities and differences between computerized information systems in terms of the availability of the same specifications and technical characteristics and performance today is governed by market supply and customer demand. At handed recent study concluded that a set of recommendations that will reflect the dimensions of the impact on investment decisions, information systems, accounting computerized or words technician more accurate for the purposes of the study, it increased controls increases the reliability of accounting information, which represents the output of accounting information system users have lists and financial data, as well as for another package that will improve the computerized accounting information systems on the levels of production, marketing, development, change, implementation and follow-up, in order to carry users of financial reports to investors, especially whom to trust the results of the accounting software and delivery the healthy work with their outputs.